Evaluasi Penggunaan Dana Bantuan Operasional Sekolah (BOS) di Smp Negeri 1 Bengkulu Selatan - Lidya Nataliya; Harius Eko Saputra; Evi Lorita; Bando Amin C. Kader (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
Hajj registration services are a form of public service that has an important role in ensuring administrative order and certainty of the departure of pilgrims. Along with the increasing number of prospective pilgrims every year, the Ministry of Religious Affairs of the Republic of Indonesia implements the Integrated Hajj Computerized Information System (SISKOHAT) as an information technology-based hajj registration service system. However, in its implementation, various obstacles are still found that affect the quality of service. This study aims to evaluate the Hajj registration service through the SISKOHAT application system at the Hajj and Umrah Service Office in Bengkulu City. This study uses a qualitative method with a descriptive approach. The data collection technique was carried out through observation, interviews, and documentation with informants from employees of the Hajj and Umrah Implementation Section. Data analysis uses the CIPP (Context, Input, Process, Product) evaluation model to assess the overall implementation of services. The results of the study show that in the context component, the implementation of SISKOHAT is in accordance with the needs of hajj registration services. In the input component, there are still limitations of human resources and supporting facilities. In the process component, the service has not run optimally due to network and application system disruptions. Meanwhile, in the product component, the use of SISKOHAT provides convenience and transparency in Hajj registration, although it is not fully optimal. Therefore, it is necessary to improve the quality of the network, strengthen human resources, and update the system to improve the quality of Hajj registration services.